Preparation of Regenerated Cellulose Fiber from Bamboo Fiber - Yao, Shuangquan; Nie, Shuangxi; Niu, Fenjie; Xue, Guoxin; Wang, Shuangfei (Asian Journal of Chemistry, 2014)
This work discusses preparation technology research based on bamboo raw material of regenerated cellulose fiber pulp. First make two sets of single factor analysis of hot water extraction hemicellulose: single factor analysis of prehydrolysis temperature, single factor analysis of prehydrolysis time. Then formulate the conditions of cooking, the highest cooking temperature, holding time, alkali amount with cooking, cooking vulcanization degrees this four factors, each factors change three conditions, the design becomes four factors, three conditions of orthogonal experiment. Then the results of the experiment test, main have potassium permanganate basically has value, the white degree and a-the fiber content on average, DP, etc. According to the experimental results concluded the optimal process conditions. An optimum process condition in the process of prehydrolysis is at 150 °C, time of 180 min. The best cooking technology conditions of cooking is the highest temperature 155 °C, holding time 150 min, alkaline 27 %, 25 % degree of vulcanization.